Experiences of Sexual Violence during Childhood: Becoming Survived and Recovery Institution - Iskandar, Livia (Yayasan Jurnal Perempuan, 2016)
WHO stated that “One in Three” women have experienced physical or sexual trauma globally (WHO, 2013). Statistics show that girls and women are not safer in their own homes as perpetrators are usually their intimate others or family members (Indonesian National Commission Anti Violence Against Women, 2015). Sexual violence experienced during childhood years/stage of development is likely to leave traumatic scars into adulthood if left untreated. Research in the US and Australia had indicated that survivors of sexual violence during childhood years are more susceptible to revictimization of other gender-based violence in later stage of their lives. Survivors of sexual violence are usually reluctant to report thus living silently with their trauma for years or even decades. Incest survivors found it especially hard to report their traumatic incidents because their perpetrators are family members or those familiar or with easy access around the family house/area. Research also indicated that sexual coercion showed the most negative impact compared to other traumatic coercions. Clinical and counseling psychologists with human rights perspectives need to be available to provide professional services to prevent further life trauma to survivors of sexual violence. Family therapy or a systemic approach should be an option to also provide a supportive environment as well to manage stigma from the family or from society attached to those with history of sexual violence. Services need to be strengthened, which also include interventions for perpetrators of sexual violence.